Predicting of Temporal-Spatial Sand Dunes Transition Caused by Marine Storms (Case Study: The Coast of Makran, Iran) - Soleiman PirouzZadeh; Mahmood Khosravi; Samad Fotohi (تحقیقات کاربردی علوم جغرافیایی)
Studies show that 14 provinces are impacted by wind erosion and the movement of sand dunes. The sand originated from the shores of Oman Sea is the most important environmental hazards that threaten the already large number of rural settlements. Sands of marine origin are available on the beach and away from the sea of dunes in addition of marine origin, Predictive models for planning sustainable use of land use and land cover in a country like Iran that land use is changing rapidly, there is an urgent need; To detect and predict changes in land cover changes overview to better manage natural resources and protect marginal lands beaches and is very effective long-term policy measures. The aim of this paper is  modeling and prediction of changes in  land-use in 2035 by using  CA Markov model and Landsat satellite images in the West of Zarabad,( The coasts of Makran). Then to determine the changes in the movement of sand dunes in the study area ranged from twenty-three years (1991-2014), satellite imageries from Landsat 7 and 8(ETM+ sensor) with 15 and 30 meters spatial resolution , was used. The 1991, 2001and 2014 month August images were used, this images from website of the US Geological Survey (USGS) have been prepared. Finally, these images by using Geographic Information System (GIS), ENVI and IDRISI softwares were analyzed. The results  showed that the changes in the region the largest increase in the interest of sand dunes in the year 1991 (25.561) km², in 2001 (10 . 568) km², and in 2014 (45.578), and the increase of (17.198) km², has experienced. The results also estimated that in future (2035) sand dunes area increase to 592.45 km².This  increase in area of sand dunes occur in the absence of proper and efficient management is done in order to stabilize the sand. This increase resulted from changed moorland 162 km²of land area (27%) and 12 kilometers of vegetation (2%) and 23 km² of fluvial (3.4%). These changes makes heavily exposed about 6 villages (Karti,Gnjk, Sohroki, Pyvshk, Vanak and Kalirak) to the movement of running sands.